P342 Assessment Of The Recommendations Structure In Eight Clinical Practice Guidelines Developed In Colombia. (15th August 2013) - Florez, I; Perez, A; Prieto, L; Cañon, L
Abstract : Background: There is not enough information to guide editorial wording of recommendations within CPG (Clinical Practice Guidelines) development. The AGREE-II instrument suggests the inclusion of population, intervention and outcome (P-I-O) components within recommendations. Objective: To evaluate P-I-O component in CPG recommendations and to analyse its relationship with the AGREE-II evaluation. Methods: Eight recently developed in Colombia CPG were chosen and assessed by four methodological experts; the presence of P-I-O component in each recommendation was established, and compared with an external evaluation score of the 15th item of AGREE-II instrument. Results: Eight guidelines with a total of 691 recommendations were evaluated, all of them were appraised by external international review with the Spanish AGREE-II instrument and its use were recommended. An average of 9.9% of recommendations met P-I-O structure; the absence of each component was 31.2% for population, 6% for intervention and 85.2% had no outcome. The item 15 of AGREE-II instrument reported results between 4 and 7, scores of good quality. Discussion: Recommendations in CPG seem to be clear, but most of them don't contain the evaluated criteria for their report. External evaluation emphasises in clarity of recommendation, and there is no agreement with the percentages obtained according to P-I-O structure, which enhance its understanding. Implications: It is advisable to standardise methodology for recommendations to include all components that reflect the answer to the research question.